Functional analysis of auxin derived from a symbiotic mycobiont - Chen, Cheng-Yen; Selvaraj, Poonguzhali; Naqvi, Naweed I. (Frontiers in Plant Science, 2023)
The biosynthesis of auxin or indole-3-acetic acid by microorganisms has a major impact on plant-microbe interactions. Several beneficial microbiota are known to produce auxin, which largely influences root development and growth in the host plants. Akin to findings in rhizobacteria, recent studies have confirmed the production of auxin by plant growth-promoting fungi too. Here, we show that Penicillium citrinum isolate B9 produces auxin as deduced by Liquid chromatography tandem-mass spectrometry analysis. Such fungal auxin is secreted and contributes directly to enhanced root and shoot development and overall plant growth in Arabidopsis thaliana. Furthermore, auxin production by P. citrinum likely involves more than one tryptophan-dependent pathways. Using auxin biosynthesis inhibitor L-Kynurenine, we show that the indole-3-pyruvate pathway might be one of the key biosynthetic routes involved in such auxin production. Confocal microscopy of the DR5rev:GFP Arabidopsis reporter line helped demonstrate that P. citrunum B9-derived auxin is biologically active and is able to significantly enhance auxin signaling in roots during such improved root growth and plant development. Furthermore, the phenotypic growth defects arising from impaired auxin signaling in Arabidopsis taa1 mutant or upon L-Kynurenine treatment of wild-type Arabidopsis seedlings could be significantly alleviated by fungus B9-derived auxin, thus suggesting its positive role in plant growth promotion. Collectively, our results provide clear evidence that the production of auxin is one of the main mechanisms involved in induction of the beneficial plant growth by P. citrinum.